Hora do conto na creche com A história engatada - Neves, Luana Silva [UNESP]; Souza, Renata Junqueira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents one of contações the project Time of the Center's Tale in Reading and Children's and Youth Literature "Maria Coelho Silva Betty" (CELLIJ), FCT / Unesp, which aimed to provide listeners with the Creche Anita Ferreira Braga de Oliveira pleasure, developing captivating them playfulness and interest in reading and literature. Thus, in Bebeteca the institution was the storytelling with pictures for children 2-4 years of the history Engaged, Sylvia Orthof. Before that, however, there was a selection of history, technique to be used and the making of the enlarged prints, as well as testing and study of narrative to work with young readers and listeners from the proposal of Solé reading strategies ( 1998), focusing times before, during and after reading. As a result, it is observed that the Engaged History at the Creche aroused the interest of small listeners, making them associate the narrative to real life and to have fun to honor the storytelling.

Este texto apresenta uma das contações do projeto Hora do Conto do Centro de Estudos em Leitura e Literatura Infantil e Juvenil “Maria Betty Coelho Silva” (CELLIJ), da FCT/Unesp, que teve por objetivo proporcionar aos ouvintes da Creche Anita Ferreira Braga de Oliveira prazer, desenvolvendo neles ludicidade e cativando o interesse pela leitura e literatura. Desse modo, na Bebeteca da instituição houve a contação com gravuras para as crianças de 2 a 4 anos da História Engatada, de Sylvia Orthof. Antes, no entanto, houve a seleção da história, da técnica a ser utilizada e a confecção das gravuras ampliadas, bem como ensaios e estudo da narrativa para se trabalhar com os pequenos leitores e ouvintes a partir da proposta das estratégias de leitura de Solé (1998), privilegiando momentos antes, durante e depois da leitura. Como resultados, observa-se que a História Engatada na Creche despertou o interesse dos pequenos ouvintes, fazendo com que estes associassem a narrativa à vida real e se divertissem ao prestigiar a contação.
Keywords: Small listeners; Children's literature; Education; Pequenos ouvintes; Literatura infantil; Educação